The influence of intercropping Paris polyphylla with Polygonatum cyrtonema or Ganoderma lucidum on rhizosphere soil microbial community structure and quality of Paris polyphylla - Su, Hailan; Liao, Penghui; Chen, Hong; Lin, Fengfang; Zheng, Meixia; Niu, Yuqing; Ye, Wei; Mao, Fanghua; Zhu, Yujing; Fang, Yanghui; Zhu, Yanming (Frontiers in Microbiology, 2025)
IntroductionProlonged monoculture cultivation of Paris polyphylla has been linked to challenges such as disruption of rhizosphere soil microbial balance and deterioration in crop quality. Intercropping has emerged as a viable strategy to address these issues.MethodsIn the present study, monoculture of P. polyphylla (PP) served as the control, while two intercropping systems were implemented: P. polyphylla with Polygonatum cyrtonema (PPPC) and P. polyphylla with Ganoderma lucidum (PPG). The objective was to evaluate the P. polyphylla quality, soil physicochemical properties, and the structure of the microbial community.ResultsFindings revealed that the PPG intercropping system significantly increased available potassium levels by 50.28% and enhanced the abundance of Trichoderma by 3,022% via the G. lucidum network. These alterations were associated with improvements in P. polyphylla yield (51.30%), polyphyllin VII content (34.16%), and total polyphyllin content (30.59%). Conversely, the PPPC system promoted the enrichment of Cupriavidus and nitrogen-fixing bacteria such as Hyphomicrobiales, leading to a 26.78% rise in available phosphorus and a 20.00% increase in polyphyllin II content in P. polyphylla. Both intercropping approaches markedly elevated the abundance of Basidiomycota, with the PPPC system further enriching functional microbial taxa including Glomeromycota and Saitozyma.DiscussionCollectively, these results demonstrate that intercropping P. polyphylla with either P. cyrtonema (PPPC) or G. lucidum (PPG) enhances soil physicochemical attributes, optimizes the composition of rhizosphere microbial communities, and positively influences the accumulation and yield of bioactive compounds.